2022
DOI: 10.21468/scipostphys.12.1.026
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dynamics of the $O(4)$ scalar theory within the fRG approach

Abstract: In this paper, the real-time dynamics of the O(4)O(4) scalar theory is studied within the functional renormalization group formulated on the Schwinger-Keldysh closed time path. The flow equations for the effective action and its nn-point correlation functions are derived in terms of the "classical'' and "quantum’’ fields, and a concise diagrammatic representation is presented. An analytic expression for the flow of the four-point vertex is obtained. Spectral functions with different values of temperature and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 77 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…One can see that when temperature is large, one has a negative spectral function in the regime of small p 0 , and there is a minus peak structure around the pole mass. It is found that the negative spectral function results from the contributions of the Landau damping, and see [277] for a more detailed discussion. Nonetheless, when the temperature is decreased below about 60 MeV, the Landau damping is dominated by the process of creation and annihilation of particles, and the spectral function is positive.…”
Section: Spectral Functions and Dynamical Critical Exponentmentioning
confidence: 97%
See 4 more Smart Citations
“…One can see that when temperature is large, one has a negative spectral function in the regime of small p 0 , and there is a minus peak structure around the pole mass. It is found that the negative spectral function results from the contributions of the Landau damping, and see [277] for a more detailed discussion. Nonetheless, when the temperature is decreased below about 60 MeV, the Landau damping is dominated by the process of creation and annihilation of particles, and the spectral function is positive.…”
Section: Spectral Functions and Dynamical Critical Exponentmentioning
confidence: 97%
“…In this section we would like to discuss the fRG formulated on the Keldysh path at the example of the O(N ) scalar theory [277].…”
Section: Real-time Frgmentioning
confidence: 99%
See 3 more Smart Citations